Reconstruction of Islamic Family Law in Facing Household Dynamics of Generation Z in the Digital Era - Aisha Inda Nursifa; Alfitozaki Jundi Robbany Akmal Fauzan; Devi Zahrotul Ulya; Khansa Naila Nurhusna; Intan Marhenisaputri Novitasari (PT. Nawa Edukasi Nusantara, 2026)
This study discusses the reconstruction of Islamic family law in addressing the dynamics of Generation Z households in the digital era, which is characterized by rapid social change. The purpose of this study is to analyze the shifting meaning of marriage among Generation Z and to examine the challenges of Islamic family law in responding to these changes in a contextual manner. The method used is qualitative research with a library research approach through the analysis of various literature related to Islamic family law, Generation Z, and the impact of digitalization on social life. The results of the study show that Generation Z experiences a shift in marriage values from sacred aspects toward rational-pragmatic considerations influenced by economic conditions, psychological factors, and exposure to digital media. The “marriage is scary” phenomenon reflects an increasing fear of the institution of marriage due to social construction in digital media. This study concludes that a more adaptive, contextual, and responsive reconstruction of Islamic family law is needed without abandoning its fundamental principles of Sharia.